Uma leitura do mítico-simbólico feminino na tessitura do imaginário paimiano em A casa da coruja verde, de Alina Paim - Parente, Monique Martins (2023)
This research aims to identify the mythical-symbolic representation of the feminine in A Casa da Coruja Verde, by Alina Paim, a work republished in 2019, maintaining the original characteristics of the 1962 publication. Brazilians, and their search for knowledge and formal education in the face of social spaces characteristic of the capitalist system. From this point of view, the possible meanings of the mythological and symbolic elements invoked by the work to represent the feminine in Catita are questioned, considering the dialogue with the horizon of readers of children's literature. It is established as a starting point, then, to investigate the mythical-symbolic referents in the corpus that make up Paim's representation of the feminine in the face of capitalist society, as constitutive elements of the narrative. In this process, there will be a mythoanalysis of the myths shared by Greco-Roman society and of symbolic representations observed in the study of the feminine archetypes. It is intended, therefore, to relate the mythical-symbolic and archetypal manifestations as an appeal to the wonderful that seeks involvement in children's and youth literature in the face of social issues. The research will consider the preponderant social mechanisms through which the intellectual and labor restriction of the female occurs, in order to reflect Paim's literature in its resistance to gender inequality. With this, the hypothesis of the mythical heroic journey is taken, with Catita understood as the personification of the brazilian feminine in search of autonomy, as a resource to discuss women's access to education and understanding of the social engenderings that surround work. To this end, a qualitative investigation will be conducted, starting from exploratory and biobibliographical research, whose theoretical-methodological basis will be structured taking as a guide the approach to myth and the feminine in the studies of Joseph Campbell (2013), Eleazar Mielietinski (1987), Clarissa Pinkola Estés (2018), among others; as well as the conceptions of childhood and children's literature according to Nelly Novaes Coelho (2012), Regina Zilberman (2005) and Philippe Ariès (1986). Furthermore, the socio-historical approach to the feminine proposed by Heleieth Saffioti (2013) and Michelle Perrot (2008) is axes for formulating the problems and hypotheses in this dissertation.